Air-broadening in near-infrared carbon dioxide line shapes: Quantifying contributions from O2, N2, and Ar. (August 2021) - Adkins, Erin M.; Long, David A.; Hodges, Joseph T.
Highlights: Frequency-agile rapid scanning cavity ring-down spectroscopy was used to measure air-broadening in the (30012) ← (00001) carbon dioxide (CO2 ) band up to J ʺ = 50. Synthetic air samples with varying levels of nitrogen, oxygen, and argon combined with multi-spectrum fitting allowed for the collisional broadening terms of each major air component to be simultaneously determined in addition to advanced line shape parameters at atmospherically relevant CO2 mixing ratios. The ability to constrain experimental data with theoretical results (e.g. rCMDS) can reduce scatter in the | m |-dependence of line shape parameters derived from multi-spectrum fits of advanced line profiles. Abstract: We measured air broadening in the (30012) ← (00001) carbon dioxide (CO2 ) band up to J ʺ = 50 using frequency-agile rapid scanning cavity ring-down spectroscopy. By using synthetic air samples with varying levels of nitrogen, oxygen, and argon, multi-spectrum fitting allowed for the collisional broadening terms of each major air component to be simultaneously determined in addition to advanced line shape parameters at atmospherically relevant CO2 mixing ratios. These values were compared to broadener-specific line shape parameters from the literature. Fits to measured spectra were also constrained with results from requantized classical molecular dynamic simulations. We show that this approach enables differentiation between narrowing mechanisms in advanced line shape parameters retrieved from experimental spectra of limited signal-to-noise ratio.